(untitled) (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Turnover intention, the likelihood of leaving a job, is a global challenge in nursing, affecting healthcare stability. Job satisfaction, a positive attitude toward job stability and professional growth, plays a crucial role in retaining nurses and ensuring quality care.This study aims to identify turnover intention and job satisfaction level among nurses. Method: A mixed-method descriptive cross-sectional study design with a simple random sampling technique, select 422 nurses from a tertiary-level hospital in Lalitpur, Nepal. Data were collected from 408 nurses using the Job Satisfaction Survey (JSS) and Turnover Intention Scale (TIS-6) from January to March 2024. Data were analyzed using SPSS 16 for quantitative data, descriptive statistics for socio-demographics, job satisfaction, and turnover intention levels. A chi-square test examined the association between turnover intention and job satisfaction. Thematic analysis was done for open-ended questions. Result: More than half, 243(59.6%), reported ambivalence, 123(30.10%) were satisfied, and 42(10.30%) were dissatisfied with their jobs. Additionally, 205(50.20%) reported turnover intention, while 203(49.8%) did not. There was a significant association between turnover intention and job satisfaction among nurses in the tertiary-level hospital (p<0.001). Conclusion: Most of the respondents revealed ambivalence regarding job satisfaction, and half expressed turnover intention. The significant association highlights the need for targeted interventions to enhance job satisfaction such as improving workplace conditions, fostering supportive management, and implementing retention strategies to reduce turnover intention.